2015
DOI: 10.1111/cas.12806
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase moonlights: Therapeutic targets beyond telomerase

Abstract: Telomeres, the repetitive sequences at chromosomal ends, protect intact chromosomes. Telomeres progressively shorten through successive rounds of cell divisions, and critically shortened telomeres trigger senescence and apoptosis. The enzyme that elongates telomeres and maintains their structure is known as telomerase. The catalytic subunit of this enzyme (telomerase reverse transcriptase [TERT]) is expressed at a high level in malignant cells, but at a very low level in normal cells. Although telomerase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 72 publications
(140 reference statements)
2
48
0
Order By: Relevance
“…Flow cytometry studies showed that, at 48 h post-transfection the number of total apoptotic cells was significantly increased. There are several pathways involved in hTERT mediated apoptosis; this can be telomerase dependent pathways such as Bax/Bcl-2 pathway, PI3 k/Akt pathway (Wang et al 2012;Shi et al 2014) or telomerase independent pathways (non-canonical) like DNAdamage repair, WNT/b-catenin signaling, NF-jB signaling and regulation of mitochondrial activity (Chiodi and Mondello 2011;Maida and Masutomi 2015). However, our results cannot conclude whether the apoptosis is mediated through hTERT dependent or independent pathway.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Flow cytometry studies showed that, at 48 h post-transfection the number of total apoptotic cells was significantly increased. There are several pathways involved in hTERT mediated apoptosis; this can be telomerase dependent pathways such as Bax/Bcl-2 pathway, PI3 k/Akt pathway (Wang et al 2012;Shi et al 2014) or telomerase independent pathways (non-canonical) like DNAdamage repair, WNT/b-catenin signaling, NF-jB signaling and regulation of mitochondrial activity (Chiodi and Mondello 2011;Maida and Masutomi 2015). However, our results cannot conclude whether the apoptosis is mediated through hTERT dependent or independent pathway.…”
Section: Discussionmentioning
confidence: 68%
“…Telomerase consists of telomerase RNA (hTR) and the catalytic component human telomerase reverse transcriptase (hTERT) for telomeric DNA synthesis. Evidence from the previous studies shows that, beyond the telomeric DNA synthesis activity, TERT is involved in several other functions including tumor development, cell proliferation, gene expression regulation and mitochondrial functionality (Chiodi and Mondello 2011;Maida and Masutomi 2015). It also plays a major role in stem cell maintenance and cell reprogramming processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells frequently activate the expression of telomerase reverse transcriptase (hTERT) to maintain telomere ends of DNA (Maida & Masutomi 2015). The ability of hTERT peptides to induce cancer cell-specific cytotoxic T cell activity was explored in the phase III TeloVac study.…”
Section: Vaccinesmentioning
confidence: 99%
“…There are conflicting results regarding the association between the TERT SNPs and telomere length in leukocytes [28,30]. However, variants in the TERT promoter region (rs2853669 and rs2735940) and intron 4 (rs10069690) are likely to affect telomere length in leucocytes or noncancerous tissues [31,32]. The rs2853669 SNP is associated with ADC risk (rs2853669, odds ratio (OR) = 1.38); however, neither rs2853669 nor rs10069690 is statistically associated with ADC risk in the Japanese population (OR=1.06 and 1.07, respectively) [11].…”
Section: Gwas Of Lung Cancer Riskmentioning
confidence: 99%